EFFECT OF REMOVAL OF CHOLESTEROL DIET UPON SERUM SICKNESS-CHOLESTEROL-INDUCED ATHEROSCLEROSIS - Van Winkle, M. (The Rockefeller University Press, 1968)
In this report, the role of vascular allergy (i.e., hypersensitivity) in the potentiation of atherogenesis has been studied. In order to accomplish this, bovine serum albumin (BSA) was administered to rabbits in quantities sufficient to cause the occurrence of serum sickness (a type of hypersensitivity known to cause injury to the endothelial linings of certain blood vessels). This was immediately followed by the feeding of a special cholesterol-supplemented diet, which is known to be capable of initiating a high incidence of atheromatous disease in rabbits after prolonged feeding. Results indicated that those animals which received the combined treatment developed an incidence of pathology after only 2 wk of special diet which was not equaled in the diet-only control groups until they had been treated for 4 wk. This indicated that vascular allergy could potentiate lipemia-induced atherogenesis in the rabbit, and was in confirmation of an earlier study of a similar nature. Indeed, because of the relatively mild vascular injury caused by a single injection of BSA, it would seem as though vascular hypersensitivity was extremely effective in the potentiation of atherogenesis. In addition, these results may have given some indication of the degree of vascular injury necessary for the induction of irreversible atheromatous disease. While the incidence of lesions in serum sickness controls was seen to decrease with passage of time after BSA challenge, it appeared to increase after cessation of treatment in those animals which received the combined treatment of BSA plus 2 wk of cholesterol-supplemented diet. It would therefore appear that the atheromatous lesions seen as early as 2 wk after initiation of the experiment may already have been irreversible in terms of the resolution of established pathology.